2011
DOI: 10.1002/elan.201100399
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Catalase‐Based Amperometric Biosensor for the Determination of Increased Catalase Content in Milk Samples

Abstract: The aim of our work was to develop a selective amperometric biosensor for infected milk detection. The catalase enzyme (EC 1.11.1.6) was immobilized onto the surface of a thin-layer enzyme cell. The measurements were carried out in stopped-flow injection analysis system (0.8 mL min À1 flow rate, + 590 mV polarization potential) in organic phase (6 % sodium acetate buffer 200 mM pH 6.0, ferrocene conductive salt (7.5 mg L À1 ) dissolved in acetonitrile. A certain amount of hydrogen peroxide was degraded by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Staphylococcus [202] Food [203,204], Medical [205], Pharmaceutical [206,207], Bioremediation [208] Bacillus species [218]. Trichoderma, Penicillium, Aspergillus [219,220] Pulp and paper, food, textile and feed [221] Food preservation with organic acids (e.g., Lactic acid)…”
Section: Intense Yellowmentioning
confidence: 99%
“…Staphylococcus [202] Food [203,204], Medical [205], Pharmaceutical [206,207], Bioremediation [208] Bacillus species [218]. Trichoderma, Penicillium, Aspergillus [219,220] Pulp and paper, food, textile and feed [221] Food preservation with organic acids (e.g., Lactic acid)…”
Section: Intense Yellowmentioning
confidence: 99%
“…Duarte et al had also developed a biosensor that couples immune assay with magnetic nanoparticles [56]. Fűtő et al developed selective amperometric methods that could sense the presence of spoilt and affected milk [57]. The spore-based biosensor is another novel strategy that has been developed to detect the presence of contaminants, including aflatoxins, antibiotics and microbial pathogens in milk.…”
Section: Detection Of Animal Poultry and Dairy Pathogensmentioning
confidence: 99%
“…Ashley and Li (2013) also contributed in quantifying the amount of bovine catalase in milk using an SPR aptasensor. It has been previously reported that the presence of this protein in bovine milk serves as a biomarker for the detection of mastitis disease in milk samples (Fűtő et al, 2012;Lansbergen et al, 1994).…”
Section: Mass-sensitive Aptasensorsmentioning
confidence: 99%